Antibiotic-antiapoptotic dual function of clinacanthus nutans (Burm. F.) lindau leaf extracts against bovine mastitis - Aussara Panya (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Mastitis caused by bacterial infection has negative impacts on milk quality and animal health, and ultimately causes economic losses to the dairy industry worldwide. Gram-negative bacteria and their component lipopolysaccharide (LPS) can trigger the inflammatory response of endothelial cells (ECs) and subsequently promote EC dysfunction or injury, which is a critical pathogenesis of mastitis-causing sepsis shock. To control the bacterial infection and to minimise the LPS negative effects on ECs, we thus aimed to identify the potential herb extracts that comprised antibacterial activity and protective ability to inhibit LPS-induced cell death. Extracts from seven types of herbs derived from antibacterial screening were investigated for their protective effects on LPS-stimulated bovine endothelial cell line. Clinacanthus nutans (Burm. f.) Lindau (C. nutans) extract appeared to be the most effective antiapoptotic extract against LPS stimulation. Treatment of C. nutans extract in LPS-stimulated cells significantly lowered apoptotic cell death through modulating pro-survival Bcl-2 and pro-apoptotic Bax expression. The investigation of bioactive compounds using solvent fractionation, HPLC, and LC-MS/MS analysis revealed glyceryl 1,3-disterate (C39H76O5), kaempferol 3-O-feruloyl-sophoroside 7-O-glucoside (C43H48O24), and hydroxypthioceranic acid (C46H92O3) as the candidate components. Our findings indicated that C. nutans extract has great potential to be further developed as an alternative therapeutic agent for mastitis treatment.